Research on the Couch : Single-case studies, subjectivity and psychoanalytic knowledge. - Hinshelwood, R. D. (New library of psychoanalysis. 'Beyond the Couch' series., 2013)
Is psychoanalysis knowledge? Is psychoanalysis a science, or is it hermeneutics? Can clinical material be considered research data?Psychoanalysis is ambiguous about whether it is about meaning or about truth, and the relations between these two compelling experiences. Psychoanalysts often think of their work as closer to the humanities than to medical and natural science. The wider the gap between science and psychoanalysis appears, the more psychoanalysts feel pulled to something that respects subjectivity, the humanity of their patients themselves, and move away from the procedures.